Heidi's children - Tritten, Charles; Goldsborough, June; Spyri, Johanna, 1827-1901. (New York, Golden Press, 1967)
A sequel to the author's Heidi grows up, which is a continuation of Johanna Spyri's Heidi. Tells of the birth of Heidi's twins, the child Marta who comes to live with Heidi and her family, and the Alm-Uncle's secret.
Keywords: Switzerland -- Fiction